5 Manganese enhanced MRI can quantify myocardial infarct size earlier than gadolinium enhanced MRI. (March 2019) - Jasmin, NH; Zaw-Thin, M; Lythgoe, MF; Davidson, S; Stuckey, DJ
Abstract : Introduction: Late gadolinium enhanced MRI (LGE-MRI) can quantify infarct size after myocardial infarction (MI) but is non-specific and reflects the increased membrane rupture and extracellular space that develop post MI. 1 Mn is a potent T1-contrast agent that enters myocytes through active calcium channels, thus reducing T1 in viable myocardium. 2 This active process rapidly ceases under ischemia. Hence, we hypothesised that Mn-enhanced MRI (MEMRI) could quantify final infarct size earlier than LGE-MRI. Methods: Myocardial infarction was induced in 7 mice which then underwent MEMRI (n=4, 0.1 mmol/kg MnCl2 ) or LGE-MRI (n=3, 0.5 mmol/kg Gd-DTPA) at 1 hour post MI. All animals then underwent both MEMRI and LGEMRI at ∼24 hours post MI with a contrast washout period of at least 5 hours between scans. Imaging was performed using a 9.4T Agilent MRI system and a multi-slice inversion recovery sequence in the short-axis orientation covering the whole left ventricle TE/TR=3.04/1.11 ms, TI=∼600 ms for MEMRI and ∼350 ms for LGE-MRI, 90 0 excitation pulse, slice thickness=1.0 mm, FOV=25.6 × 25.6 mm, matrix size=128 × 128) as described. 3 Results: At 1 hour post MI, viable myocardium was enhanced in MEMRI, allowing early delineation of the occlusion zone as 41%±8% of the myocardium, whereas only subtle enhancement was seen on LGE-MRI, yielding a significantly lower value of 12%±2% (p=0.03. Figure 1 ). At ∼24 hours post MI, the MEMRI measure of infarct size remained constant (41%±5%) whilst LGE-MRI significantly increased to a level comparable with MEMRI (37%±3%). Figure 2 shows a direct comparison of MEMRI and LGE-MRI acquired in the same animal at 22 and 27 hours after MI, respectively, with matching histological TTC staining for infarct size. Discussion: Effected myocytes rapidly stop internalising Mn under ischemic conditions, allowing early delineation of the occlusion zone. The membrane rupture that underlies LGE-MRI occurs later, meaning LGE-MRI underestimates the occlusion zone during the first hours post MI. Conclusions: The present study shows MEMRI can quantify final infarct size earlier than LGE-MRI. This provides a sensitive approach which could be used as an early measure of cell death and myocardial viability when assessing the efficacy of new drugs which target acute MI. References: . Doltra A, Amundsen BH, Gebker R, Fleck E, Kelle S. Emerging concepts for myocardial late gadolinium enhancement MRI. Current Cardiology Reviews2013;9:185. . Waghorn B, Schumacher A, Liu J, Jacobs S, Baba A, Matsuda T, Hu TC-C. Indirectly probing Ca(2+) handling alterations following myocardial infarction in a murine model using T(1)-mapping manganese-enhanced magnetic resonance imaging. Magnetic Resonance in Medicine2011;65:239. . Chow A, Stuckey DJ, Kidher E, Rocco M, Jabbour RJ, Mansfield CA, Darzi A, Harding SE, Stevens MM, Athanasiou T. Human induced pluripotent stem cell-derived cardiomyocyte encapsulating bioactive hydrogels improve rat heart function post myocardial infarction. Stem Cell Reports 2017;9:1415.